Critical Phenomena: Towards Modeling with Cellular Automata - Wiśniewski, Andrzej (Studia Informatica. System and information technology, 2007)
The paper presents basic description methods of critical phenomena, i.e. first-order, continuous phase transitions, and an overview of the self-organized criticality concept. In this approach an attempt is made to identify the determinant factors of modeling critical events using cellular automata.